(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2022)
Introduction: Women living with Vesico Vaginal Fistula (VVF) continue to suffer for many years, and often in silence. Around the world, over 2 million women live with a fistula and new cases continue to be reported especially in low income countries. These countries also tend to have a high maternal morbidity and mortality rates. Objectives: To establish the duration of leakage in a cohort of women diagnosed with fistula. Methodology: A prospective cohort study conducted over a three-year period. Patients with confirmed diagnosis of VVF and or Recto Vaginal fistula (RVF) were eligible for study. A structured questionnaire was used to collect information on sociodemographic profiles, presenting symptoms and duration of leakage. Results: A total of one thousand and twenty-four patients were enrolled in the study, 34% had lived with the fistula for more than 3 years. The majority (70%) were young, with a mean age of 20. Literacy levels were low in this cohort. Urban women were more likely to access fistula care services compared to their rural counterparts (p>0.0001). Conclusion: Individual and country level factors influenced the duration women lived with fistula before surgical repair.